Antirasismens Andra - Rickard Jonsson (Educare)
The category of the “immigrant student”, which is often used in the educational setting from where the following study collects its data, is indeed an elusive one – especially so when it is employed as a label of students who have no experience of migration at all. The frequent use of the category is even more confusing, considering that Swedish publicity could be described as characterized by a hegemonic anti-racist discourse, including an often reproduced master narrative of a country which – except from a few right wing extremists – is considered to be a nation without racism. Drawing on linguistic ethnographic data from a fieldwork in a high prestigious secondary school in inner city Stockholm, this article examines how narratives of an unruly classroom behavior become associated with ”the young immigrant student” category, and furthermore, how students rhetorically manage the dilemma to tell that story without sounding disparaging. The paper is an investigation of anti-racist waysoftalkingaboutfailing students as the ethnic or racial Others.